Among the hidden / 1. - Haddix, Margaret Peterson (Shadow Children, 2000)
In a future where the Population Police enforce the law limiting a family to only two children, Luke has lived all his twelve years in isolation and fear on his family's farm, until another "third" convinces him that the government is wrong.